Role of Fe doping on structural and electrical properties of MnO2 nanostructured thin films for glucose sensing performance. (October 2020) - Zahan, Muslima; Podder, Jiban
Abstract: Iron (Fe) doped manganese dioxide (MnO2 ) nanostructured thin films (Fe: MnO2 ) were prepared by a spray pyrolysis deposition technique to explore their morphological, structural, and electronic properties suitable for glucose sensing abilities. Many useful characteristics were observed in the growth process and phase transformation due to the addition of Fe concentration in the range of 0–8 at %. Fe concentration strongly influenced the crystallite size of MnO2 analyzed by field emission scanning electron microscope. Powder X-ray diffraction (PXRD) pattern of the deposited thin films showed the tetragonal crystal structure with a body-centered space group (I41 /acd) having lattice parameters a = b = 9.787 Å and c = 2.865 Å and well agrees with the JCPDS card file no. 44–0141. Crystallite size was measured ranging from 20 nm to 30 nm using Debye Scherer relation. Williamson-Hall plot results indicated the appearance of strain for Fe doping. Maximum carrier concentration was found at 4 at% Fe concentration using Hall Effect measurement. The highest glucose-sensing response was recorded at about 29% at 5 min for 4 at% Fe concentration.